Parasitological and serological investigation into lymphatic filariasis among immigrants at Semenyih Detention Centre, Selangor, West Malaysia - Abdullah, Wan Omar; Abdullah, Khairul Anuar; O., Sulaiman; Noordin, Rahmah; A., Manaf; A., Rahimah (Faculty of Medicine, University of Malaya, 2000)
Parasitological and serological investigations for lymphatic filariasis were performed on 450 immigrants detained at the Immigration Centre at Semenyih, Seiangor, West Malaysia. The country of origin of these immigrants were Indonesia, The Philippines, Myanmar, Bangladesh, India and Pakistan. Brugia malayi adult worm homogenate (BmAH) antigen was used for the detection of antifilarial IgG. A monoclonal antibody-based ELISA (MAb.XC3~ELISA) specific for filarial circulating antigens and non-phosphorylcholine reactive was used to detect antigenemia in these immigrants. Parasitologically 67 (14.89 %) were positive for W, bancrofti and 54 (12.0%) for Brugia malayi. Serologically 63 % had antifilarial IgG titre to the BmAH antigen. While Bancroftian filariasis is now unknown in Peninsular Malaysia, the potential of it to be reintroduced into Peninsular Malaysia by the immigrant population is discussed.